Can Reading the Life of a Self-Abusive Visionary Make Sense Today? - Mary Frohlich (Religions)
The Autobiography of Saint Marguerite-Marie Alacoque recounts her many visions, ecstasies, and sufferings as she became God’s messenger, initiating the highly successful modern form of devotion to the Sacred Heart. Reading the Autobiography today is difficult, however. She constantly practices forms of obedience, self-control, and self-abuse that are offensive to today’s sensibilities. Her image of Jesus is as her “Master’ and “Sovereign” who desires and demands suffering on the part of those who love him. Her theology of the necessity of repairing God’s wounded honor by suffering is likewise outdated. Finally, the reliance of her message on visions does not inspire trust in an era that generally views visions as symptoms of pathology. This essay proposes that it is possible to discover authentic inspiration in the Autobiography by reading it with the help of several mediating theories. First, Hubert Hermans’ Dialogical Self Theory offers insight into traditional, modern, and postmodern styles of self-construction, thus situating Alacoque’s stories and practices within her time (at the cusp between traditional and modern styles) while offering a glimpse of how she can be understood within our time (at the cusp between modern and postmodern styles). Second, a historically contextualized eucharistic theology of embodied self-giving helps to see past the problematic elements of her theology. Finally, an ecotheological theory of visions suggests a way to understand her visions that may unveil their significance for our own time of crisis.